2023
DOI: 10.3390/pathogens12060839
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors of Mycobacterium tuberculosis as Modulators of Cell Death Mechanisms

Abstract: Mycobacterium tuberculosis (Mtb) modulates diverse cell death pathways to escape the host immune responses and favor its dissemination, a complex process of interest in pathogenesis-related studies. The main virulence factors of Mtb that alter cell death pathways are classified according to their origin as either non-protein (for instance, lipomannan) or protein (such as the PE family and ESX secretion system). The 38 kDa lipoprotein, ESAT-6 (early antigen-secreted protein 6 kDa), and another secreted protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 165 publications
1
3
0
Order By: Relevance
“…Here, we showed that early infection with virulent Mtb begins with small foci of infection stemming from the upper airways, which eventually disseminates to the lower areas of the lung. This is in line with studies that have shown that Mtb virulence proteins drives tissue destruction early on and allows infected macrophages to depart the primary granuloma and disseminate the infection 27 .…”
Section: Discussionsupporting
confidence: 89%
“…Here, we showed that early infection with virulent Mtb begins with small foci of infection stemming from the upper airways, which eventually disseminates to the lower areas of the lung. This is in line with studies that have shown that Mtb virulence proteins drives tissue destruction early on and allows infected macrophages to depart the primary granuloma and disseminate the infection 27 .…”
Section: Discussionsupporting
confidence: 89%
“… 37
Figure 2 Mechanisms of UA for anti-TB agent using computational methods (reproduced with permission from Ref. (Ramon-Luing et al, 2023), 38 ©2023 Pathogens; (Sundararajan and Muniyan, 2021), 39 ©2021 Molecular Biology Reports; (Jacobo-Delgado et al, 2023), 40 ©2023 Frontiers in Immunology. Created with Biorender.com.
…”
Section: Ua As a New Treatment For Tuberculosis: Current Progressmentioning
confidence: 99%
“…It is interesting to note that MTB is extremely adapted to survive under the extreme conditions that lie within the macrophages and other cells of the immune system. In addition to possessing an incredible capacity to modulate not only its metabolism and cell division under these conditions but also, manipulate the immune responses of the host [16,118,180,[217][218][219][220].…”
Section: Who Are Mtb? the Genes Answer The Questionmentioning
confidence: 99%